PENGGUNAAN INTERNET SEBAGAI MEDIA BARU DALAM DAKWAH: PELUANG DAN TANTANGAN DI ERA DIGITAL - Azka Husna Fajri, Mohammad (ASWALALITA: Journal of Da'wah Management, 2024)
In the era of globalization, the Internet has become a crucial means of communication, playing a significant role in spreading the message of Islamic da'wah. This article explores the role of the internet as a new medium for Islamic da'wah efforts. It discusses the advantages offered by the internet, such as accessibility to information, interactivity, and its broad global reach. However, it also highlights challenges, particularly the issue of negative online behavior. The article demonstrates successful examples of internet use in Islamic da'wah and analyzes the challenges faced by preachers in the digital space. In this context, the role of individuals, including ustadz and preachers, is emphasized, focusing on their use of various platforms and adherence to proper preaching ethics. Through this discussion, the article aims to provide insights into strategic steps for enhancing the effectiveness of da'wah via the internet. Key strategies identified include improving digital literacy, adopting innovative da'wah methods, and fostering inter-institutional collaboration. By examining both the challenges and opportunities, this article contributes to a deeper understanding of the internet's role in spreading Islamic teachings in the digital age.